The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14237205
|View full text |Cite
|
Sign up to set email alerts
|

Water Treatment from MB Using Zn-Ag MWCNT Synthesized by Double Arc Discharge

Abstract: A new type of nano-adsorbent zinc-silver nanoparticles ornamented by multi-walled carbon nanotubes (Zn-Ag MWCNT) was efficiently synthesized by double arc discharge using a newly designed rotating cylinder electrode. Zn-Ag MWCNT was characterized by different instrumental methods to get information about the sample shape, size, and crystallinity. Without irradiation, Zn-Ag MWCNT indicated significant potential for elimination against methylene blue (MB) which is dissolved in deionized water. When the adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…As shown in Figure 2 Figure 2a represented small Zn-NPs size surrounding MWCNT compared with our previous work [32] which may be due to the change of some physical parameters such as rotational speed of the cathode and voltage of power supply [18,33]. On the other hand Figure 2b showed that MWCNT inner radius was smaller than the previous work despite of their larger outer radius (compared with others).…”
Section: Nanoparticles Fabricationmentioning
confidence: 71%
“…As shown in Figure 2 Figure 2a represented small Zn-NPs size surrounding MWCNT compared with our previous work [32] which may be due to the change of some physical parameters such as rotational speed of the cathode and voltage of power supply [18,33]. On the other hand Figure 2b showed that MWCNT inner radius was smaller than the previous work despite of their larger outer radius (compared with others).…”
Section: Nanoparticles Fabricationmentioning
confidence: 71%
“…The most classical type of used carbonaceous adsorbent for water treatment are activated carbons, which can be under granular or powdered forms. Yet, other types of preparation can be conducted, as illustrated in the study by Aljohani et al, in which the authors synthetized multi-walled carbon nanotubes (MWCNTs) adorned with Zn and Ag NPs (nanoparticles) [ 5 ]. The preparation of the adsorbent, through the double arc discharge method, allowed cheap production costs, a major limitation for the technology transfer from research to companies.…”
Section: Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…This Special Issue (SI) contains the successful submissions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] of Materials on the subject area of “New Materials and Technologies for Wastewater Treatment”. The development of new materials that are able to enhance the efficiency of industrial wastewater treatment processes, as well as the modulation of these materials’ properties to improve the recovery of pollutants, has experienced steady progress.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, bimetallic NPs composed of MWCNT are widely used for removing pollutants from aquatic mediums. [ 13–16 ] This shows that the bimetallic NPs contaminate the aquatic environment. Therefore, it is necessary to reveal the toxic effects of this newly synthesized NP in aquatic environments.…”
Section: Introductionmentioning
confidence: 98%